Enhancing the physical stability and supersaturation generation of amorphous drug-polyelectrolyte nanoparticle complex via incorporation of crystallization inhibitor at the nanoparticle formation step: A case of HPMC versus PVP - Dong, Bingxue (2020)
Amorphous drug-polyelectrolyte nanoparticle complex (or nanoplex in short) has emerged as a highly attractive solubility enhancement strategy of poorly-soluble drugs attributed to its simple and highly efficient preparation. The existing nanoplex formulation, however, exhibits poor amorphous form stability during long-term storage for drugs with high crystallization propensity. Using ciprofloxacin (CIP) and sodium dextran sulfate (DXT) as the model drug-polyelectrolyte nanoplex, we investigated the feasibility of incorporating crystallization inhibiting agents, i.e. hydroxypropyl methylcellulose (HPMC) and polyvinylpyrrolidone (PVP), at the nanoplex formation step to improve the physical stability of the CIP nanoplex. The effects of the HPMC or PVP additions on the nanoplex's physical characteristics (i.e. size, zeta potential, CIP payload), CIP utilization rate, dissolution rate, and supersaturation generation were also examined. The results showed that the additions of HPMC or PVP increased the CIP nanoplex size (from 300 to 500 nm) and CIP utilization rate (from 65% to 90% w/w) with minimal impacts on the CIP payload (70-80% w/w). Their additions had opposite impacts on the nanoplex's colloidal stability due to surfactant nature of PVP. Significantly, unlike the CIP-DXT and CIP-DXT-PVP nanoplexes, the CIP-DXT-HPMC nanoplex remained amorphous after three-month accelerated storage, while also exhibited superior solubility enhancement (15-30% higher).